Basic income : a guide for the open-minded - Standing, Guy (New Haven : Yale University Press, 2017)
Basic income is a revolutionary idea that guarantees regular, unconditional cash transfers from the government to all citizens. It is an acknowledgement that everyone plays a part in generating the wealth currently enjoyed by only a few and would rectify the recent breakdown in income distribution. Political parties across the world are now adopting this innovative policy and the idea generates headlines every day. Guy Standing has been at the forefront of thought surrounding basic income for the past thirty years, and in this book he covers in authoritative detail its effects on the economy, poverty, work, and labor; dissects and disproves the standard arguments against basic income; explains what we can learn from pilots across the world; and illustrates exactly why basic income has now become such an urgent necessity.
Basic income : its meaning and historical origins -- Basic income as social justice -- Basic income and freedom -- Reducing poverty, inequality and insecurity -- The economic arguments -- The standard objections -- The affordability issue -- The implications for work and labour -- The alternatives -- Basic income and development -- Basic income initiatives and pilots -- The political challenge : how to get there from here -- Appendix: How to run a basic income pilot -- List of BIEN-affiliated organizations.
Includes bibliographical references (pages 323-348) and index.
Print version record.
JSTOR
Keywords: Basic income; Income; Income distribution; Revenu annuel garanti; Revenu; Revenu -- Répartition.; BUSINESS & ECONOMICS -- Economics -- Macroeconomics; POLITICAL SCIENCE -- Economic Conditions; BUSINESS & ECONOMICS / Economics / General; Basic income; Income; Income distribution; Garantiertes Mindesteinkommen; Electronic book